Auditor Industry Specialization and Evidence of Cost Efficiencies in Homogenous Industries - Bills, Kenneth L.; Jeter, Debra C.; Stein, Sarah E. (The Accounting Review, 2015)
ABSTRACT This study examines the audit pricing effects when auditors specialize in industries conducive to transferable audit processes. Our results indicate that industry specialists charge incrementally lower fees in industries with homogenous operations, and particularly in industries with both homogenous operations and complex accounting practices. Moreover, we discover that audit quality is no lower for clients audited by these specialists offering fee discounts, consistent with a conclusion that the reduction in fees indicates cost efficiencies rather than lower-quality audits. Further analysis indicates that the shared economies of scale only occur in a subsample of client firms with relatively high bargaining power. When considered in conjunction with prior research using a survivorship approach, our study provides evidence that certain industries lend themselves to specialization because auditors generate cost-based competitive advantages without compromising service quality. Data Availability: Data are publicly available from the sources identified in the paper.